Pembelajaran Berbasis dalam Jaringan (Daring) pada Masa Pandemi Covid 19 - Tamrin, Muhammad; Dwiyana, May Vira (Al-Fikru: Jurnal Ilmiah, 2020)
This study aims to analyze online-based learning during the Covid 19 pandemic and the role of parents during the online learning process. This research was conducted at private SD Yaspenhan-1 Medan Marelan. This research uses qualitative research methods based on descriptive studies. The data was collected by means of interview techniques, observation and documentation study. Data analysis through data presentation techniques and drawing conclusions. Test the validity of the data using tringulation and methods. The results showed that online-based learning at the Private SD Yaspenhan-1 Medan Marelan made effective online-based learning media such as what app, e-learning, Google Class Room, zoom and other applications. The role of parents in online-based learning is very significant to improve learning outcomes. This role is in the form of supervision of children's learning activities at home. Without supervision, it will be difficult to maximize children's learning outcomes.